Research on mechanical properties and thermo-mechanical fatigue behaviours of Mg-12Gd-3Y-0.5Zr magnesium alloy at elevated temperatures - Yang Xiao Ming (MATEC Web of Conferences, 2016)
In this paper, tensile and thermo-mechanical fatigue tests were carried out on Mg-12Gd-3Y-0.5Zr magnesium alloy at elevated temperatures. It shows that Mg-12Gd-3Y-0.5Zr magnesium alloy has good mehanical properties at high temperatures and thermo-mechanical fatigue mechanism is disscussed in this paper.